‘Āʼisha Bint al-Shāṭi’s Thoughts on Tarāduf and Their Implications for the Istinbāṭ of Law - Imran, Maizul; Ismail, Ismail (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2019)
As a book containing miracles, in literature, the miracles of the Quran have been proven by ʻĀʼisha Bint al-Shāṭiʼ through her theory i‘jāz lughawī. She showed the importance of the correct method of interpretation of the Qurʼan from aspects of tarāduf (synonym). However, despite following the rule of